Simulation of advanced cataract surgery – validation of a newly developed test - Forslund Jacobsen, Mads (Acta Ophthalmol, 2020)
PURPOSE: To develop and investigate an Eyesi simulator‐based test for the more experienced cataract surgeon for evidence of validity. METHODS: The study was a prospective interventional cohort study and carried out at the Copenhagen Academy for Medical Education and Simulation. The Eyesi Simulator was used for the test which was developed by three expert cataract surgeons. Ten cataract surgeons (>250 surgeries performed) and ten ophthalmic residents performed two repetitions of the test. The test consisted of four modules: Iris Expansion Ring insertion – level 1, Iris Expansion Ring extraction – level 2, Capsulorhexis – level 3 and Anterior Vitrectomy – level 6. RESULTS: Internal consistency reliability showed Cronbach’s alpha of 0.63. Test–retest reliabilities were significant for Iris Expansion Ring extraction – level 2 (p = 0.012) and Capsulorhexis – level 3 (p = 0.018). Differences between the two groups were only significant in both repetitions for the Iris Expansion Ring extraction – level 2 (p < 0.001 and p = 0.041, respectively). Furthermore, we found a statistically significant difference between the mean module scores for novices and the more experienced surgeons for Iris Expansion Ring insertion – level 1 (p = 0.021) and Capsulorhexis – level 3 (p = 0.019) in the first repetition. CONCLUSION: The investigated modules show evidence of validity within several aspects of Messick’s framework. However, the evidence is not strong enough to apply the test for certification purposes of cataract surgeons, but the modules may still be relevant in the training of advanced cataract surgical procedures.